Knockdown MTDH Inhibits Glioma Proliferation and Migration and Promotes Apoptosis by Downregulating MYBL2 - Junqi Fu; Jun Peng; Guolong Tu (Mediators of Inflammation)
Glioma is a malignant tumor that often occurs in the adult central nervous system. Metadherin/astrocyte-elevated gene-1 (MTDH) is involved in the development of cancer, but its relationship with glioma remains unclear. This study is aimed at clarifying the role of MTDH in glioma. GEPIA was employed to find the difference of the expression level of MTDH and MYB protooncogene-like 2 (MYBL2) in glioma tissues and normal tissues, and real-time quantitative reverse transcription PCR (qRT-PCR) and western blot (WB) were applied to verify the differential gene expression of MTDH and MYBL2 cells. After knocking down of MTDH, the expressions of forkhead box M1 (FoxM1), MTDH, and MYBL2 were detected by WB cells. Cell counting kit 8 (CCK-8) was used to detect cell proliferation, and flow cytometry was applied to measure cell apoptosis. The transwell assay was utilized to investigate the ability of cell migration and invasion. The results showed that MTDH and MYBL2 were overexpressed in glioma cells compared with normal cells. The knockdown of MTDH would inhibit the expression of MYBL2 through decreasing the expression of FoxM1 and further reduce glioma cell proliferation and cell migration and invasion. The present study showed that knockdown of MTDH inhibits glioma proliferation and migration and promotes apoptosis by downregulating MYBL2, which suggests that MTDH is a potential gene in clinical treatment of glioma.